Motivation and Marketing Mix Influencing Tourists’ Buying Behavior at Ceramic Outlet Lampang Province Thailand - Harsadin Sornpala หัสดินทร์ สอนปะละ (Dusit Thani College Journal, 2018)
The purpose of this research was to study the motivation and marketing mix that influence behaviors of purchasing of ceramic at an outlet of Thai tourist consumers in Lampang province. The data were analyzed according to the research methodology 2 types; quantitative research methodology, the sample group consists of 400 respondents, and data collected by questionnaire, and qualitative research methodology, sample group consists of 15 people and data collected by interview. The research results found that Thai tourist consumers in different genders have different behaviors in purchasing ceramics at outlet in Lampang Province, differently as following; the frequency of purchasing ceramics (6 times/month) at statistical significant of .05 level. The emotional motivation and marketing mix in pricing, influence to behavior of purchasing ceramics of Thai travelers at the ceramic outlet in Lampang province. In sum of budgets that purchase ceramics at the outlet in Lampang province (baht/time) at statistical significant of .05 level. The research results from the interviews found that these ceramics were considered to be beautifully designed modern and unique; especially the Bantam design, which is the symbol of Lampang province. There are many styles or designs to support the demands of the consumer. The Lampang province is well known as famous center ceramics for manufacturing. Furthermore, most of the opinions indicated that people purchased Lampang ceramics, such as tableware and souvenirs, for their own purposes and as gifts. It would also be reasonable, for the Lampang ceramic merchants to increase the price of their products by between 5-10 baht per piece, due to the quality, of the product and their unique style.